2018
DOI: 10.3390/catal8040128
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Catalytic Ozonation of Recalcitrant Organic Chemicals in Aqueous Solution over Various ZSM-5 Zeolites

Abstract: Catalytic ozonation processes (COPs) are an emerging technology for wastewater treatments. NaZSM-5 zeolites in three different SiO 2 /Al 2 O 3 ratios (31, 45, and 120) and their metallic oxides loaded samples were compared for COP of nitrobenzene solution. NaZSM-5(120) showed high total organic carbon (TOC) removals (70.2-74.0%) by adsorption relative to NaZSM-5(45) (0.4-0.6%) at various initial pH conditions. NaZSM-5(31) was obtained by NaOH treatment of NaZSM-5(45) and displayed 20.9-23.8% of TOC removals by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…[20] 29 Si solid-state NMR 29 Si solid-state NMR of zeolite-Y was done to assess the Si/Al ratio of the zeolite NaÀ Y catalyst. The deconvoluted 29 Si solid- The peaks obtained are in good agreement with the literature. [21] The peaks obtained at À 88.73, À 93.51, À 98.84, and À 104.72 correspond to Si(3Al), Si(2Al), Si(1Al), and Si(0Al), respectively.…”
Section: Thermogravimetric (Tga) Analysismentioning
confidence: 99%
“…[20] 29 Si solid-state NMR 29 Si solid-state NMR of zeolite-Y was done to assess the Si/Al ratio of the zeolite NaÀ Y catalyst. The deconvoluted 29 Si solid- The peaks obtained are in good agreement with the literature. [21] The peaks obtained at À 88.73, À 93.51, À 98.84, and À 104.72 correspond to Si(3Al), Si(2Al), Si(1Al), and Si(0Al), respectively.…”
Section: Thermogravimetric (Tga) Analysismentioning
confidence: 99%
“…Heterogeneous catalytic ozonation is a promising technology for the degradation and mineralization of refractory pollutants in an aqueous solution . The catalysts used for this purpose mainly include (1) metal oxides (e.g., MnO 2 , , Al 2 O 3 , , CeO 2 , , and FeOOH , ); (2) silicate materials (e.g., zeolite, , MCM-41, SBA-15, and cordierite); (3) metal and metal oxides-supported catalysts (e.g., Cu/Al 2 O 3 , MnO X /Al 2 O 3 , Co/AC, and FeOOH/Al 2 O 3 ); and (4) activated carbon (AC). , Among these catalysts, γ-Al 2 O 3 -supported metal oxides show high activity for the catalytic oxidation of aromatic compounds and MnO 2 has an outstanding performance among the first transition metal. , The catalytic activity of MnO 2 is positively correlated with the number of surface hydroxyl groups and oxygen vacancies, and it can be improved by combining other metals such as Cu, Fe, and Ce oxides. , Li et al found that Cu/Mn-loaded γ-Al 2 O 3 showed enhanced catalytic activity for the removal of Acid Red B.…”
Section: Introductionmentioning
confidence: 99%
“…4 Heterogeneous catalytic ozonation is a promising technology for the degradation and mineralization of refractory pollutants in an aqueous solution. 5 The catalysts used for this purpose mainly include (1) metal oxides (e.g., MnO 2 , 6,7 Al 2 O 3 , 8,9 CeO 2 , 10,11 and FeOOH 12,13 ); (2) silicate materials (e.g., zeolite, 14,15 MCM-41, 16 SBA-15, 17 and cordierite 18 ); (3) metal and metal oxides-supported catalysts (e.g., Cu/Al 2 O 3 , MnO X /Al 2 O 3 , Co/AC, and FeOOH/Al 2 O 3 ); 19−22 and (4) activated carbon (AC). 23,24 Among these catalysts, γ-Al 2 O 3supported metal oxides show high activity for the catalytic oxidation of aromatic compounds and MnO 2 has an outstanding performance among the first transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous catalytic ozonation, utilizing several minerals as catalysts, has been previously reported to remove efficiently different emerging organic pollutants via the acceleration of hydroxyl radicals production [3]. Minerals, such as zeolite [4], anatase [5], kaolin [6] and calcite [7], are shown satisfactory performances as catalysts in this process.…”
Section: Introductionmentioning
confidence: 99%